2010
DOI: 10.1021/es902799f
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Effects of Prenatal and Neonatal Exposure to PFOS in Developing Rat Brain

Abstract: Perfluorooctane sulfonate (PFOS), a persistent and bioaccumulative compound, is widely distributed in the environment. To explore the molecular mechanism of neonatal neurotoxic effects, we evaluated the transcriptional effects of prenatal and neonatal exposure to PFOS in developing rat brain by performing gene expression profiling in the cerebral cortex. Dams received 3.2 mg/kg PFOS in their feed from gestational day 1 (GD1) to weaning (PND 21). Pups then had free access to treated feed until PND 35. Six Illum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 43 publications
1
39
0
Order By: Relevance
“…Recent studies on PFAAs in rodents have found that neonatal exposure to PFOS or PFOA can cause disruption to the central nervous system, resulting in abnormal development of motor neurons and significant changes in gene expression, including genes responsible for calcium signaling pathways, peroxisome proliferator-activated receptor signaling, cell communication, and the cell cycle [25]. Other symptoms included deranged spontaneous behavior, hyperactivity that worsened with age, changes in exploratory behavior, and reduced muscle strength in males [26].…”
Section: Possible Toxicological Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies on PFAAs in rodents have found that neonatal exposure to PFOS or PFOA can cause disruption to the central nervous system, resulting in abnormal development of motor neurons and significant changes in gene expression, including genes responsible for calcium signaling pathways, peroxisome proliferator-activated receptor signaling, cell communication, and the cell cycle [25]. Other symptoms included deranged spontaneous behavior, hyperactivity that worsened with age, changes in exploratory behavior, and reduced muscle strength in males [26].…”
Section: Possible Toxicological Implicationsmentioning
confidence: 99%
“…Furthermore, exposure concentrations in these studies far surpass concentrations found in free-ranging wildlife. For example, Wang et al [25] administered PFOS both prenatally and neonatally in albino Wistar rats. They showed that at birth (day 1) the PFOS concentration in the brain of pups was 2.085 AE 0.108 mg/g wet weight and over 840 genes were significantly affected.…”
Section: Possible Toxicological Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…PPARs have been shown to be involved in the control of proliferation, differentiation and migration of NSCs (Cimini and Ceru, 2008), and PFOS has been suggested to exert its effects via PPAR signaling (Wang et al, 2010). To clarify the mechanisms of PFOS-induced alterations of differentiation, we examined the mRNA expression of PPARs (PPARα, PPARδ and PPARγ) and their downstream targets; the mitochondrial uncoupling proteins (UPC1, UCP2 and UCP3) controlling the energy conversion in the mitochondria (Villarroya et al, 2007), and the superoxide dismutases (SOD1, SOD2, SOD3) which are important enzymes in the antioxidant defence system of cells (Bordet et al, 2006) (Table 1).…”
Section: Pfos Activation Of the Nuclear Receptor Pparγmentioning
confidence: 99%
“…Takacs and Abbott (2007) have shown that PFOS significantly increased the activation of mouse PPARα and PPARδ isoforms, but not PPARγ, in Cos-1 cells using transient transfection assay. A study on the transcriptional effects of prenatal and neonatal exposure of rat to PFOS using gene expression profiling in the cerebral cortex, showed that PPARs are among the affected signaling pathways (Wang et al, 2010). The effects of PFOS on the three isoforms of PPARs have been shown in marine medaka fish, Oryzias melastigma, where exposure to PFOS first inhibited the expression of PPARα and PPARδ at early developmental stage (dpf 4), and then induced it at later stage (dpf 10), while no changes were observed in PPARγ expression at either stage (Fang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%